2021
DOI: 10.1177/2156759x211053825
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating With Families to Address Cyberbullying: Exploring School Counselors’ Lived Experiences

Abstract: Limited research has focused on exploring the collaboration between home and school to address cyberbullying. In this qualitative study, we interviewed 17 school counselors to explore their experiences working with parents and caregivers in addressing cyberbullying. We identified four themes: (a) connections with parents and families, (b) digital citizenship, (c) blurred boundaries, and (d) family/counselor support. We discuss the themes and offer implications for school counselors to address cyberbullying in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…In the school environment, administrators and staff would benefit from participating in professional development efforts that potentially reduce bullying and violence among students. Creating opportunities for school staff and students to collaborate in efforts toward increasing school belonging and social‐emotional skill‐building has promise for reducing rates of bullying and violence (Cross et al, 2015; Espelage, 2014; Su et al, 2021). At the community level, efforts need to go beyond schools, as low levels of neighborhood safety were noted for youth in the High Risk‐Low Protection profile in our sample, consistent with past research (Taliaferro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the school environment, administrators and staff would benefit from participating in professional development efforts that potentially reduce bullying and violence among students. Creating opportunities for school staff and students to collaborate in efforts toward increasing school belonging and social‐emotional skill‐building has promise for reducing rates of bullying and violence (Cross et al, 2015; Espelage, 2014; Su et al, 2021). At the community level, efforts need to go beyond schools, as low levels of neighborhood safety were noted for youth in the High Risk‐Low Protection profile in our sample, consistent with past research (Taliaferro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research that focuses on prevention and solving issues through education as the basis and emphasizes the collaboration of family networks provides significant findings. Su and colleagues examined the role of families and schools in preventing cyberbullying in their study (Su et al, 2021). The focus is placed on the administration of student care and mentoring systems.…”
Section: Previous Research Studiesmentioning
confidence: 99%
“…Strengthening bystander competencies to address cyberbullying behavior among peers and improving school climate is another potential intervention strategy (Lindstrom Johnson et al, 2013) and a potential RMC extension. In qualitative interviews, school counselors reported a spillover effect of cyberbullying into schools and suggested that further support materials for parents, digital citizenship training for youth, and support for school counselors and teachers are needed (Su et al, 2021). Scholars have suggested incorporating social and emotional interventions promoting positive relationships into the school curriculum, focusing on improving relationships among peers and the relationships between adults and students (Bradshaw & Waasdorp, 2019; Cohen & Geier, 2010).…”
Section: Implications For Prevention and Future Researchmentioning
confidence: 99%
“…Cyberbullying prevention has been found to be effective in promoting healthier online interactions with peers in school settings at the school-wide, classroom-wide, small group, and individual levels (Doty et al, 2021). At the school-wide level, teachers and administrators are encouraged to have discussions regarding online safety and appropriate online activities (Su et al, 2021). Strengthening bystander competencies to address cyberbullying behavior among peers and improving school climate is another potential intervention strategy (Lindstrom Johnson et al, 2013) and a potential RMC extension.…”
Section: Implications For Prevention and Future Researchmentioning
confidence: 99%